2017
DOI: 10.1075/lia.8.1.03car
|View full text |Cite
|
Sign up to set email alerts
|

The development of iconicity in children’s co-speech gesture and homesign

Abstract: Gesture can illustrate objects and events in the world by iconically reproducing elements of those objects and events. Children do not begin to express ideas iconically, however, until after they have begun to use conventional forms. In this paper, we investigate how children’s use of iconic resources in gesture relates to the developing structure of their communicative systems. Using longitudinal video corpora, we compare the emergence of manual iconicity in hearing children who are learning a spoken language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Experiment 4 showed that gesture comprehension was immune to the way that children learned about the action (through observation or experience), suggesting that the difference between conditions is not due to gestures being more informative because they relate to multiple aspects of experience simultaneously. This pattern resonates with other research, finding that action‐based gestures, like the ones we used here, are especially suited to establish reference in the absence of language (Cartmill, Rissman, Novack, & Goldin‐Meadow, ; Fay, Lister, Ellison, & Goldin‐Meadow, ; Ortega, Sümer, & Özyürek, ). Ortega et al.…”
Section: Discussionsupporting
confidence: 90%
“…Experiment 4 showed that gesture comprehension was immune to the way that children learned about the action (through observation or experience), suggesting that the difference between conditions is not due to gestures being more informative because they relate to multiple aspects of experience simultaneously. This pattern resonates with other research, finding that action‐based gestures, like the ones we used here, are especially suited to establish reference in the absence of language (Cartmill, Rissman, Novack, & Goldin‐Meadow, ; Fay, Lister, Ellison, & Goldin‐Meadow, ; Ortega, Sümer, & Özyürek, ). Ortega et al.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the iconic and body-anchored representation of locative forms to express spatial relations in TİD, deaf children still need early exposure to be able to benefit from iconicity in these forms for acquiring descriptions of view-dependent relations. Thus, iconicity cannot be taken for granted (see Cartmill et al, 2017). Our findings show that late signers do need early sign language input to benefit from iconic forms.…”
Section: Late Sign Language Exposure Hinders the Acquisition Of Exprementioning
confidence: 75%
“…Morford et al 1997) demonstrate this point through a direct comparison of classifier verbs elicited from the well-known homesigner David both before and after he began acquiring ASL in his late teens. The grammatical sophistication of David's homesign system is particularly well-documented (Morford and Goldin-Meadow, 1997;Hunsicker and Goldin-Meadow 2012;Cartmill et al, 2017), including his systematic use of certain handshape classifiers to represent objects with specific sizes and shapes (Goldin-Meadow et al, 1995). Yet, despite the impressive homesign system he had created as a child, which included mechanisms for encoding different types of objects through handshape, David's subsequent acquisition of this aspect of ASL was not more successful than that of other deaf late-learners Mayberry, 1993).…”
Section: Theoretical Consequences Of Recognizing the Initial System Within The Crip Linguistics Perspectivementioning
confidence: 99%